Imagining Hedda Gabler: Munch and Ibsen on Art and Modern Life - Gjesdal, Kristin (Text Matters: A Journal of Literature, Theory and Culture, 2017)
Among Edvard Munch’s many portraits of Henrik Ibsen, the famous Norwegian dramatist and Munch’s senior by a generation, one stands out. Large in scope and with a characteristic pallet of roughly hewed gray blue, green and yellow, the sketch is given the title Geniuses. Munch’s sketch shows Ibsen, who had died a few years earlier, in the company of Socrates and Nietzsche. The picture was a working sketch for a painting commissioned by the University. While Munch, in the end, chose a different motif for his commission, it is nonetheless significant that he found it appropriate to portrait the Norwegian dramatist in the company of key European philosophers, indeed the whole span of the European philosophical tradition from its early beginnings to its most controversial spokesman in the late 1800s. In my article, I seek to take seriously Munch’s bold and original positioning of Ibsen in the company of philosophers. Focusing on Hedda Gabler—a play about love lost and lives unlived—I explore the aesthetic-philosophical ramifications of Ibsen’s peculiar position between realism and modernism. This position, I suggest, is also reflected in Munch’s sketches for the set design for Hermann Bahr’s 1906 production of the play.